Transnational Activism in the Post‑Digital Networks of the Bound Art Book Fair and the Hackney Comic + Zine Fair - Preston, Louisa (Mémoires du livre / Studies in Book Culture, 2022)
The author’s experiences of the Hackney Comic + Zine Fair (HCZF) and the Manchester‑based Bound Art Book Fair (BABF) are the point of departure for this article. The discussion focuses on the distinctiveness of these spaces of dissemination and the positioning of the agents involved. This article shows how virtual engagement at each fair became entangled with situated experiences and printed publications. The article also considers the significance of an autoethnographic approach within the post‑digital context, and its relationship to pursuing scholarly activism within twenty‑first‑century book studies. HCZF and BABF operate in post‑digital networks of artist‑ and self‑publishing; this positionality allows them to advocate for change and social justice. Transnational activism is evidenced through the accessibility, resources, and community empowerment that these fairs offer and generate for creative publishing practices. HCZF and BABF evidence resistance to major book fair networks, e.g., in Frankfurt, and London, whilst simultaneously influencing and infiltrating those very networks.